Subordination of the Dalang Wayang Krucil in the National Political Constellation - Irawanto, Rudi (KnE Social Sciences, 2023)
Dalang Wayang Krucil is an important figure in practical political culture in Indonesia. In several areas in Java, especially in East Java, puppeteers are part of political forces that have very significant influence at the grassroot level. Dalang Wayang Kayu is affiliated with several political organizations that influence the ideology of this performance. In the Old Order era, there were two cultural organizations that became the shelter for puppeteers, namely Lekra and LKN. Lekra (People’s Cultural Institute) is a cultural organization under the PKI (Indonesian Communist Party), while LKN (National Cultural Institute) is under the auspices of the PNI (Indonesian National Party). The ideological confrontation between the two mass organizations affected the style of the dalang’s performances. The puppeteers under Lekra perform more populist plays, while the dalangs in LKN perform more within the context of national culture. In its development, the puppeteers, who are members of Lekra, try to close themselves off from the outside world until the end of their lives. Meanwhile, the puppeteers in the LKN continued to work until the New Order era. The subordination of puppeteers to wooden puppets is one of the factors causing the art of wooden puppets to not develop in several areas in Java. Keywords: Wayang Krucil, political constellation